2014
DOI: 10.1002/2013ja019225
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of magnetic reconnection and Kelvin‐Helmholtz modes for large magnetic shear: 2. Reconnection trigger

Abstract: Citation:Ma, X., A. Otto, and P. A. Delamere (2014) Abstract A typical property of magnetopause reconnection is a significant perpendicular shear flow due to the fast streaming magnetosheath plasma. Therefore, the magnetopause represents a large magnetic and flow shear boundary during periods of southward interplanetary magnetic field, which can be unstable to Kelvin-Helmholtz (KH) modes and to magnetic reconnection. A series of local three-dimensional MHD and Hall MHD simulations is carried out to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…The effect of outof-plane flow has been studied [44][45][46][47] . Incorporating diamagnetic effects into the theoretical predictions 48,49 should be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of outof-plane flow has been studied [44][45][46][47] . Incorporating diamagnetic effects into the theoretical predictions 48,49 should be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigates the process where a nonlinear ideal instability (i.e., the KH instability) triggers a secondary nonideal evolution (i.e., the tearing mode or more precisely component magnetic reconnection), which requires the presence of nonzero resistivity only in the diffusion region. Hence, we applied a current‐dependent resistivity model, which is given by η(j)=η0j2jc2H(jjc)+ηb (Nykyri & Otto, , ; Ma et al, , ). Here H ( x ) is the Heaviside unit step function (Arfken et al, ), the critical current density, j c , is set to be 0.4, and 1.4, the coefficient η 0 =0.2, and background resistivity, η b , is 0.002.…”
Section: Methodsmentioning
confidence: 99%
“…However, Ebert et al [] recently observed Hall magnetic field structures and Alfvénic jets at Jupiter's magnetopause near the dawn terminator, indicating that reconnection may yet play a role in mass transport. Kelvin‐Helmholtz vortices, which are observed at other planetary magnetospheres [ Hasegawa et al , ; Masters et al , ; Delamere et al , ; Sundberg et al , ; Gershman et al , ; Kavosi and Raeder , ; Ma et al , , , ], are expected to be present, but these structures at Jupiter have not yet been reported. Finally, low‐frequency MHD fluctuations with periods up to ~100 s have been observed inside of Jupiter's magnetosphere and in the magnetopause boundary layer (MPBL) [ Tsurutani et al , ].…”
Section: Introductionmentioning
confidence: 99%